Perceived Determinants of Career Choice of MBA Graduates: A Case of Higher Management Academic Institutions, Pokhara, Nepal - Ghimire, Sabina; Dhungana, Bharat Ram; Budhathoki, Dipika Sunar; Subedi, Chet Narayan; Acharya, Tara Nath (Nepalese Journal of Management and Technology, 2025)
Abstract Career path decisions among graduates are crucial for higher academic institutions. The studyaims to investigate the factors that affect career decisions among MBA graduates of thePokhara Valley. The study focuses on five major aspects of career decisions: intrinsic factors,extrinsic factors, interpersonal factors, institutional factors, and career decision self-efficacy.A primary survey of 211 purposively selected MBA graduates from the Pokhara Valley wasconducted using an explanatory research design. Descriptive and inferential statisticalanalyses have been conducted to assess the impact of each factor on career decisions. Theresults indicate that intrinsic, extrinsic, interpersonal, institutional, and career decision self-efficacy factors are correlated with graduates' career choices. Career decisions are influenced by various personal, social, economic, and institutional factors. Self-efficacy and extrinsic factors have the most significant positive impact on career choices. Higher academic institutions may strengthen career counseling services, exposure programs, and collaboration between universities and industry.